Children's sleep, impulsivity, and anger: shared genetic etiology and implications for developmental psychopathology. (14th September 2020) - Miadich, Samantha A.; Shrewsbury, Amanda M.; Doane, Leah D.; Davis, Mary C.; Clifford, Sierra; Lemery‐Chalfant, Kathryn
Abstract : Background: Prior research has established links between poor sleep and problems in emotion regulation. Impulsivity and anger/frustration are core features of child psychopathology. Further, sleep problems are commonly associated with psychopathology. This study examined shared and unique genetic and environmental influences on sleep, impulsivity, and anger/frustration in the middle childhood period with potential ramifications for psychopathology. Methods: Families (29.9% monozygotic, 38.6% same‐sex dizygotic, 31.5% opposite‐sex dizygotic) from a longitudinal twin study participated ( N  = 613 twins). Twins ( M age  = 8.37, SD  = 0.66; 49% female; 58% non‐Latinx European American, 30% Latinx) wore actigraph watches for seven days to assess sleep. Primary caregivers (95.3% mothers) completed standardized questionnaires to assess twins' temperament (impulsivity, anger/frustration). Results: Univariate ACE twin structural equation models indicated strong genetic influences (76%) on impulsivity, whereas the largest proportion of variance in anger/frustration was attributed to the shared environment (56%). Bivariate model fitting indicated that sleep—impulsivity and sleep—anger/frustration associations in children are genetic; thus, a mutual underlying genetic factor likely contributes to the commonality in these associations. Conclusions: Given evidence that sleep problems, impulsivity, and anger/frustration are mechanisms associated with psychopathology, our findings suggest a genetic commonality and the need to focus on shared and unique risk factors when understanding etiology. Early intervention and prevention efforts should target both sleep problems and high levels of impulsivity and anger/frustration in children, which may have implications for later psychopathology.